A Framework on Polarization, Cognitive Inflexibility, and Rigid Cognitive Specialization - Wu, James Shyan-Tau; Hauert, Christoph; Kremen, Claire; Zhao, Jiaying (Frontiers in Psychology, 2022)
Polarization is pervasive in the current sociopolitical discourse. Polarization tends to increase cognitive inflexibility where people become less capable of updating their beliefs upon new information or switching between different ways of thinking. Cognitive inflexibility can in turn increase polarization. We propose that this positive feedback loop between polarization and cognitive inflexibility is a form of threat response that has benefited humans throughout their evolutionary history. This feedback loop, which can be driven by conflict mindset, group conformity, and simplification of information, facilitates the formation of strong bonds within a group that are able to eliminate threats and increase individual fitness. Although cognitive inflexibility is conventionally seen as maladaptive, here we argue that cognitive inflexibility may be an adaptation under polarization. That is, in a highly polarized society most people only interact with members of their own social group, without having to confront perspectives from another group or interacting with out-group members. In this context, cognitive inflexibility creates rigid cognitive specialization, a set of cognitive traits that allow people to operate efficiently within their social circles but not outside of it. Although rigid cognitive specialization benefits individuals in the short term, it may lead to more polarization over the long run, and thus produce more conflict between groups. We call on future research to examine the link between cognitive inflexibility and rigid cognitive specialization.